Office‐Based Photoangiolytic Laser Treatment of Reinke's Edema: Safety and Voice Outcomes. (27th March 2015) - Koszewski, Ian J.; Hoffman, Matthew R.; Young, W. Greg; Lai, Ying‐Ta; Dailey, Seth H.
Abstract : Objective: To evaluate the safety, tolerability, and voice outcomes of office‐based photoangiolytic laser treatment of Reinke's edema. Study Design: Case series with chart review. Setting: Academic medical center. Subjects and Methods: We performed a retrospective analysis of patients undergoing office‐based laser treatment of endoscopy‐proven Reinke's edema. Safety and tolerability were evaluated by reviewing complications. Voice outcomes were analyzed by comparing pre‐ and postprocedural acoustic, aerodynamic, and Voice Handicap Index measurements. Complete data sets were not available for all subjects; sample size for each parameter is reported with the corresponding result. Results: Nineteen patients met inclusion criteria. There were no minor or major complications. Five procedures were truncated due to patient intolerance. Phonatory frequency range increased (n = 12, P =. 003), while percent jitter decreased (n = 12, P =. 004). Phonation threshold pressure decreased after treatment (n = 4, P =. 049). Voice Handicap Index also decreased (n = 14, P <. 001). Conclusion: This study represents the largest series of patients undergoing office‐based photoangiolytic laser treatment specifically for Reinke's edema. Our data suggest that this is a safe and effective modality to treat dysphonia associated with Reinke's edema, although patient intolerance of the procedure may represent a barrier.